2021
DOI: 10.1029/2021gl094032
|View full text |Cite
|
Sign up to set email alerts
|

Ground Observation of Negative Sprites Over a Tropical Thunderstorm as the Embryo of Hurricane Harvey (2017)

Abstract: Sprites are the most prominent members of lightning-induced transient luminous events (TLEs), and they result from the transient electric field (E-field) perturbation in the mesosphere driven by energetic cloudto-ground (CG) lightning strokes with large charge transfer to ground (Pasko et al., 1997). The existing ground-based observations show that in the continental region, sprites are overwhelmingly associated with positive CG strokes, while only a very small fraction (<1%) of sprites are produced by negativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…Red sprites are one primary category of transient luminous events (TLEs) appearing at altitudes of 50-90 km in the near space that are believed to be caused by intense tropospheric lightning (Pasko et al, 1997;Huang et al, 1999). In the past 3 decades, the efforts of many researchers all over the world, including numerous amateurs, have confirmed that red sprites are a fairly common phenomenon that could be produced by energetic cloud-to-ground (CG) lightning strokes spawned by various types of thunderstorms (Lyons, 1996;Huang et al, 2018a, Huang et al 2018bWang et al, 2021b, Wang et al 2021c. Coordinated observations combining with the measurement of radio-frequency (RF) electromagnetic fields radiated by sprite-producing lightning strokes have revealed many details regarding the mechanism of sprite formation in the mesosphere (e.g., Li et al, 2012;Cummer et al, 2013;Ren et al, 2019;Kuo et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Red sprites are one primary category of transient luminous events (TLEs) appearing at altitudes of 50-90 km in the near space that are believed to be caused by intense tropospheric lightning (Pasko et al, 1997;Huang et al, 1999). In the past 3 decades, the efforts of many researchers all over the world, including numerous amateurs, have confirmed that red sprites are a fairly common phenomenon that could be produced by energetic cloud-to-ground (CG) lightning strokes spawned by various types of thunderstorms (Lyons, 1996;Huang et al, 2018a, Huang et al 2018bWang et al, 2021b, Wang et al 2021c. Coordinated observations combining with the measurement of radio-frequency (RF) electromagnetic fields radiated by sprite-producing lightning strokes have revealed many details regarding the mechanism of sprite formation in the mesosphere (e.g., Li et al, 2012;Cummer et al, 2013;Ren et al, 2019;Kuo et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Simultaneous optical observations of sprites and electromagnetic measurements of lightning radiation indicated that the morphological features of sprites are closely related to the polarities and discharge process of their causative CG strokes (e.g., Lu et al., 2017; Wang et al., 2021). Numerical studies have shown the polarity asymmetry of sprites produced by + CGs and – CGs, namely, “positive sprites” and “negative sprites” (Qin et al., 2011, 2013).…”
Section: Introductionmentioning
confidence: 99%